An eight-year analysis of robotic surgery in morbidly obese women with endometrial cancer in a tertiary center in Singapore - Sabrina Lasini Gruhl; Muhammad Ashraf Yusoff; Hui Men Selina Chin; Ravichandran Nadarajah (Elsevier, 2024)
Introduction: Surgical management of endometrial cancer is a total hysterectomy, bilateral salphingo-oophorectomy and pelvic lymph node dissection (THBSO-PLND), which is a challenging surgery in the morbidly obese. Data on morbidly obese women undergoing robotic surgery is limited in Asia. We share our experience in Singapore and aim to demonstrate that robotic surgery is safe and effective in morbidly obese women with endometrial cancer. Materials and Methods: We performed a retrospective analysis of patients with BMI > 40 kg/m2, who underwent robotic surgery from January 2016 to September 2023 at the Singapore General Hospital. We recruited a total of 33 patients who underwent robotic surgery for endometrial malignancy and analysed surgical outcomes, operative complications, and survival rates. Results: The average age of patients was 53 years and mean BMI 45.7. The average operative time was 232 min and average blood loss 184 ml. 3 patients had THBSO while 27 underwent THBSO-PLND. None required conversion to laparotomy. 4 patients required a mini-laparotomy for the retrieval of bulky uterus. 12 required adhesiolysis. 6 patients had additional omentectomy done. The average inpatient stay was 4.8 days. The 1-year mortality rate is 0. However, 1 patient passed away 13 months after surgery due to complications from bowel obstruction and another passed away 39 months later due to disease recurrence. 1 patient readmitted on POD6 due to post-op ileus and another for port-site hematoma. Both were managed conservatively. Conclusion: Robotic surgery is a safe and effective alternative surgical tool for women who are morbidly obese with endometrial cancer.